Anaphylatoxin C5a Regulates 6-Sulfo-LacNAc Dendritic Cell Function in Human through Crosstalk with Toll-Like Receptor-Induced CREB Signaling - Zaal, Anouk; Dieker, Miranda; Oudenampsen, Manon; Turksma, Annelies W.; Lissenberg-Thunnissen, Suzanne N.; Wouters, Diana; van Ham, S. Marieke; ten Brinke, Anja (Frontiers in Immunology, 2017)
Activation of antigen presenting dendritic cells (DC) and the complement system are essential early events in the immune defense against invading pathogens. Recently, we and others demonstrated immunological crosstalk between signaling from receptors recognizing complement activation products and PAMPs on DCs. This affects DC effector function, as demonstrated by the finding that C5a prevents induction of proinflammatory cytokines by TLR ligands in human monocyte derived DCs. Here, we demonstrate that this regulatory crosstalk is specifically important in 6-sulfo LacNAc dendritic cells (slanDC), the most proinflammatory DC subset found in human. C5aR and TLR signaling show profound interference in the ERK/p38/CREB1 signaling pathways. C5aR signaling accelerates TLR-induced CREB1 phosphorylation both in moDC and slanDC. This is key in the regulatory effect of C5a on proinflammatory DC maturation by mediating induction of IL-10, which subsequently inhibits proinflammatory cytokine production via negative feedback signaling. Importantly, the regulatory effect of C5a affects T cell immunity by decreasing Th1 and cytotoxic CD8 T cell responses. The finding that the proinflammatory effector function of slanDC can be down modulated by activation products of the complement system highlights the existence of intricate regulatory interactions between various arms of the immune system. Intensive immune monitoring of patients suffering from complement-mediated diseases or patients receiving complement modulating compounds can give more inside in the contribution of complement receptor and TLR crosstalk in APCs in disease.